Relación entre características placentarias y somatometría del recién nacido en el Hospital de apoyo Chepén – 1993 - Lozano Gonzales, Genith (1994)
150 pregnancies were studied 37 to 42 uncomplicated simple weeks a total of 344 pregnancies who attended the Maternity Hospital Service Support Chepén between the months of March to August of 1,993. This study aimed to verify the relationship between the weight of the placenta with somatometry newborn. To establish the relationship of these variables weight, height, head circumference and thoracic perimeter of the newborn was determined; and the weight of free fetal membranes placenta, umbilical cord and blood clots. The values ​​obtained regarding the characteristics and placental weight and somatometry newborn were compared with similar work by other national authors and some Latin American countries, taking result from the overall average, ie no significant difference with these results. Placental coefficient is within normal limits (Cp = 0.14). The results of the analysis loc correlation coefficients (r) indicate that there is positive correlation between placental weight and newborn somatometr1a being statistically significant.